Performance of cooling materials and their composites in maintaining freezing temperature during irradiation and transportation of bone allografts - Ramalingam, Saravana; Samsuddin, Sharifah Mazni; Yusof, Norimah; Mohd, Suhaili; Hanafi, Nurhafizatul Nadia; Ng, Wuey Min; Mansor, Azura (SAGE Publications (UK and US), 2018)
Purpose: Bone allografts supplied by University Malaya Medical Centre Bone Bank are sterilized by gamma radiation at 25 kGy in dry ice (DI) to minimize radiation effects. Use of cheaper and easily available cooling materials, gel ice (GI) and ice pack (IP), was explored. Composites of DI and GI were also studied for the use in routine trans-portations and radiation process. Methods: (a) Five dummy bones were packed with DI, GI, or IP in a polystyrene box. The bone temperatures were monitored while the boxes were placed at room temperature over 96 h. Durations for each cooling material maintaining freezing temperatures below 40°C, 20°C, and 0°C were obtained from the bone temperature over time profiles. (b) Composites of DI (20, 15, 10, 5, and 0 kg) and GI were used to pack five dummy bones in a polystyrene box. The durations maintaining varying levels of freezing temperature were compared. Results: DI (20 kg) maintained temperature below 40°C for 76.4 h as compared to 6.3 h in GI (20 bags) and 4.0 h in IP (15 packs). Composites of 15DI (15 kg DI and 9 GI bags) and 10DI (10 kg DI and 17 GI bags) maintained the temperature below 40°C for 61 and 35.5 h, respectively. Conclusion: Composites of DI and GI can be used to maintain bones in deep frozen state during irradiation, thus avoiding radiation effects on biomechanical properties. Sterile frozen bone allograft with preserved functional properties is required in clinical applications.